2022
DOI: 10.1371/journal.pone.0267842
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology and high genetic diversity amongst Cryptococcus spp. isolates infecting people living with HIV in Kinshasa, Democratic Republic of Congo

Abstract: Neuromeningeal cryptococcosis (NMC) is a life-threatening opportunistic infection in advanced HIV disease patients (AHDP). It is caused by Cryptococcus spp. complexes and mainly occurs in sub-Saharan Africa. In this study, we performed molecular characterization and antifungal susceptibility profiling of Cryptococcus isolates from AHDP in Kinshasa (DRC). Additionally, we investigated a possible association between NMC severity factors and the Cryptococcus neoformans (Cn) multilocus sequence typing (MLST) profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A minority of Cryptococcus spp. (ranging from 2–21%), are acapsular or pauci-capsular, and so untypeable [ 16 , 17 , 18 ].…”
Section: Latest On Taxonomy and Molecular Epidemiology Of Cryptococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…A minority of Cryptococcus spp. (ranging from 2–21%), are acapsular or pauci-capsular, and so untypeable [ 16 , 17 , 18 ].…”
Section: Latest On Taxonomy and Molecular Epidemiology Of Cryptococcusmentioning
confidence: 99%
“…MLST has revealed geographical associations with clonal populations with increased heterogeneity possibly related to the origins of the species; for example, C. gattii , may have spread from Australia and Northern Brazil to North America and Canada [ 28 , 29 ] whereas for C. neoformans, ST5 is the predominant serotype in China and Taiwan, ST93 in Brazil, ST41 in Japan and the US, with greater diversity in African countries [ 16 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Latest On Taxonomy and Molecular Epidemiology Of Cryptococcusmentioning
confidence: 99%
“…The long delay in CM diagnosis due to the lack of laboratory tools, the advanced stage of the patients' HIV disease on arrival at the clinics, the genetic diversity of Cryptococcus spp. and the low sensitivity of some species to common antifungal agents as previously described in DRC could partially explain this fatal outcome [17,18].…”
Section: Introductionmentioning
confidence: 89%
“…The overall data from this survey were included in our previous article. The MLST characterisation of the isolates carried out previously and allowed identification of seven different STs, including one main ST (ST93, n = 15) and six less common STs [ST659 (n = 2), ST5 (n = 2), ST4 (n = 1), ST 53 (n = 1), ST31 (n = 1), and ST69 (n = 1)] [17].…”
Section: Cryptococcus Neoformans Isolatesmentioning
confidence: 99%
“…Indirect clues about this possibility have emerged in various studies. Previous studies in Western Africa have shown that strains already resistant to fluconazole or exhibiting an elevated fluconazole MIC were present in patients naïve for this molecule in Cameroon [ 31 , 32 , 33 ], Ivory Coast [ 34 ] and DRC [ 35 ]. From a general point of view, there is increasing FCZ resistance in Cryptococcus strains isolated from Africa [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%